2019
DOI: 10.1111/febs.14989
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of N‐acetyl‐l‐glutamate kinase with the PII signal transducer in the non‐photosynthetic alga Polytomella parva: Co‐evolution towards a hetero‐oligomeric enzyme

Abstract: During evolution, several algae and plants became heterotrophic and lost photosynthesis; however, in most cases, a nonphotosynthetic plastid was maintained. Among these organisms, the colourless alga Polytomella parva is a special case, as its plastid is devoid of any DNA, but is maintained for specific metabolic tasks carried out by nuclear encoded enzymes. This makes P. parva attractive to study molecular events underlying the transition from autotrophic to heterotrophic lifestyle. Here we characterize metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
(173 reference statements)
1
27
0
Order By: Relevance
“…Moreover, there is no response towards 2-OG. Consistent with the properties of PII-NAGK activation, a metabolomic analysis revealed that P. parva accumulates significantly larger amounts of Arg and Glu than does C. reinhardtii, whereas cellular Gln concentrations are relatively low (Selim et al, 2020). Experiments with heterologous combinations of PII and NAGK proteins indicated that the effector-molecule-independent interaction is not a property of only one of the two partner proteins but instead reflects a mutual adaptation of both proteins that favours the formation of stable PII-NAGK complexes.…”
Section: Inactive Binding Sitementioning
confidence: 55%
See 3 more Smart Citations
“…Moreover, there is no response towards 2-OG. Consistent with the properties of PII-NAGK activation, a metabolomic analysis revealed that P. parva accumulates significantly larger amounts of Arg and Glu than does C. reinhardtii, whereas cellular Gln concentrations are relatively low (Selim et al, 2020). Experiments with heterologous combinations of PII and NAGK proteins indicated that the effector-molecule-independent interaction is not a property of only one of the two partner proteins but instead reflects a mutual adaptation of both proteins that favours the formation of stable PII-NAGK complexes.…”
Section: Inactive Binding Sitementioning
confidence: 55%
“…In general, PII forms an activating complex with NAGK and thereby prevents feedback inhibition by Arg (Fig. 4) (Heinrich et al, 2004;Ll acer et al, 2007;Mizuno et al, 2007b;Beez et al, 2009;Chellamuthu et al, 2014;Lapina et al, 2018;Selim et al, 2020). The crystal structures of PII-NAGK complexes from S. elongatus (PDB: 2V5H) and A. thaliana (PDB: 2RD5) and of a heterocomplex of Chlamydomonas reinhardtii PII with A. thaliana NAGK (PDB: 4USJ) have been reported.…”
Section: Inactive Binding Sitementioning
confidence: 99%
See 2 more Smart Citations
“…However, Selim et al . show that this is not the case, by studying a taxonomic outlier: The heterotrophic nonphotosynthetic unicellular alga Polytomella parva , a close relative of Chlamydomonas reinhardtii that although retaining the plastid, lacks photosynthetic pigments and plastidic DNA.…”
Section: The Reference Framementioning
confidence: 99%